THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT ON THE EFFECT OF DIVERSITY, EQUITY, AND INCLUSION (DEI) ON SOCIAL-ESG PERFORMANCE : A LITERATURE REVIEW - Sofia Yulmatri; Agung Surya Dwianto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This literature review examines the mediating role of employee engagement in the relationship between Diversity, Equity, and Inclusion (DEI) practices and corporate Social-ESG performance. Amidst the growing emphasis on ESG (Environmental, Social, and Governance) criteria, the social dimension, particularly DEI, is recognized as a strategic driver of sustainability. While prior research indicates positive links between DEI and social performance, and between DEI and employee engagement, the specific mechanism connecting these variables remains underexplored. This study synthesizes existing literature to propose and analyze a conceptual model where employee engagement acts as a key mediator. Grounded in Social Exchange Theory and the Job Demands-Resources model, the review finds that inclusive environments foster psychological safety, a sense of belonging, and empowerment, which significantly enhance employee engagement. This heightened engagement, in turn, motivates prosocial behaviors such as Organizational Citizenship Behavior, internal advocacy, and proactive innovation that directly improve measurable Social-ESG outcomes. The analysis concludes that the effect of DEI on Social-ESG performance is not merely direct but is substantially transmitted and amplified through the psychological state and subsequent behaviors of engaged employees. The study highlights the necessity for organizations to integrate DEI strategies with employee engagement initiatives to fully realize their social sustainability goals and provides a foundation for future empirical testing of this mediating relationship.